Integrating alpha, beta, and phylogenetic diversity to understand anuran fauna along environmental gradients of tropical forests in western Ecuador - Amador, Luis (2019)
The study of current distribution patterns of amphibian species in South America is of particular interest in areas such as evolutionary ecology and conservation biology. These patterns could be playing an important role in biological interactions, population size, and connectivity, and potential extinction risk in amphibians. Here, we tested the effects of spatial and environmental factors on the variation, turnover, and phylogenetic diversity of anuran amphibian species in tropical forests of western Ecuador. Data for presence/absence of 101 species of 34 genera and 10 families registered in 12 sites (nested in four biogeographic units) were obtained through fieldwork, museum collections, and literature records. We examined the influence of geographical, altitudinal, temperature, and precipitation distances on differences in anuran composition between sites. We found significant positive correlations among all of these variables with anuran distribution. The greatest alpha diversity (species richness) was found in the Equatorial Chocó biogeographic unit. Equatorial Pacific biogeographic unit could act as a transition zone between the Equatorial Chocó and Equatorial Tumbes. The western Andes (Western Cordillera biogeographic unit) was the most dissimilar and exhibited a higher species turnover rate than the other biogeographic units. Our results suggest that precipitation and elevation play a key role in maintaining the diversity of amphibian species in western Ecuador.